Compost mediates the recruitment of core bacterial communities in alfalfa roots to enhance their productivity potential in saline-sodic soils - Wei, Tian-Jiao; Li, Guang; Cui, Yan-Ru; Xie, Jiao; Teng, Xing; Wang, Yan-Jing; Li, Zhong-He; Guan, Fa-Chun; Liang, Zheng-Wei (Frontiers in Microbiology, 2024)
IntroductionComposting is one of the effective environmental protection and sustainable measures for improving soil quality and increasing crop yield. However, due to the special physical and chemical properties of saline-sodic soil and the complex rhizosphere microecological environment, the potential mechanism of regulating plant growth after applying compost in saline-sodic soil remains elusive.MethodsHere, we investigated the effects of different compost addition rates (0, 5, 15, 25%) on plant growth traits, soil chemical properties, and rhizosphere bacterial community structure.ResultsThe results showed that compost promoted the accumulation of plant biomass and root growth, increased soil nutrients, and enhanced the diversity and complexity of the rhizosphere bacterial communities. Moreover, the enriched core bacterial ASVs (Amplicon Sequence Variants) in compost treatment could be reshaped, mainly including dominant genera, such as Pseudomonas, Devosia, Novosphingobium, Flavobacterium, and Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium. The functions of these ASVs were energy resources and nitrogen cycle functions, suggesting the roles of these ASVs in improving plant root nutrient resource acquisition for alfalfa growth. The contents of available potassium, available phosphorus, total nitrogen, and organic carbon of the soil surrounding the roots, the root length, root surface area, root volume, and root tips affected the abundance of the core bacterial ASVs, and the soil chemical properties contributed more to the effect of plant biomass.DiscussionOverall, our study strengthens the understanding of the potentially important taxa structure and function of plant rhizosphere bacteria communities, and provides an important reference for developing agricultural microbiome engineering techniques to improve root nutrient uptake and increase plant productivity in saline-sodic soils.